Faktor Yang Berpengaruh Terhadap Kepatuhan Remaja Putri Dalam Mengkonsumsi Tablet Tambah Darah Di SMA Negeri 1 Kota Ternate - Hardianti, Richa Novyana; Bansu, Istiana Asrari (Barongko: Jurnal Ilmu Kesehatan, 2024)
One strategy to reduce anemia levels in adolescent girls in Indonesia is through the program of providing iron supplement tablets (TTD). In addition to minimizing the potential for anemia that affects health and achievement in school, providing iron supplement tablets also prepares the health of adolescent girls before becoming mothers, to prevent mothers from giving birth to babies with short stature (stunting) or low birth weight (LBW). The purpose of this study was to analyze the factors that influence the compliance of adolescent girls in consuming iron supplement tablets. The research design used in this study was observational analytic with a cross-sectional approach. The number of samples was 90 adolescent girls according to the inclusion and exclusion criteria of the study. The instrument used in this study was a questionnaire. Statistical analysis used Chi Square Technique analysis with a significance level of p <0.05. The results of the study concluded that the factors that influence compliance in consuming Iron Tablets in Adolescent Girls at SMA Negeri 1 Ternate City in sequence are Knowledge (p value = 0.008, OR = 6.455), Social Support (p value = 0.008, OR = 6.455), Peers (p value = 0.004, OR = 5.118) Teacher Motivation (p value = 0.005, OR = 4.750) and Health Workers (p value = 0.012, OR = 4.125) Overall, the factors studied have an influence on the compliance of adolescents at SMA Negeri 1 Ternate in consuming Iron Tablets. Supervision and assistance are needed for adolescents when consuming iron tablets and recording so that the program objectives can be achieved.